Comparative Lipid Profile Analysis of Hermetia illucens Larvae Fed Food Waste at Different Days of Age Using an LC-MS-Based Lipidomics Approach. Issue 5 (29th October 2021) - Li, Mengmeng; Wang, Guiying; Shang, Rongsheng; Xu, Qinglong; Zhang, Jincheng; Sun, Ran; Li, Lusheng
Abstract: A lipidomics approach based on liquid chromatography–tandem mass spectrometry (LC-MS) was applied to analyze the molecular-level mechanism of lipid deposition in Hermetia illucens ( H. illucens ) larvae fed food waste (FW) at different days of age. The H. illucens larvae reared on FW substrates generally became larger, heavier, and fatter at 5–15 d of age. A large amount of glycerolipids (GL) were deposited, while glycerophospholipids (GP), sphingolipids, and derivatized lipids became relatively less abundant during the growth stage of the larvae. Forty-three subclasses of 3, 205 lipid molecules were identified in larvae, and 139 lipids (79 upregulated and 60 downregulated during larval growth and development) were identified as potential biomarkers (variable importance in projection > 1; P < 0.05). The differential lipids were mainly enriched in 19 metabolic pathways, of which 9 metabolic pathways related to lipids, including GL and GP metabolisms. The results demonstrate that the lipid composition and mechanisms changed during the growth and development stage of H. illucens larvae. To the best of our knowledge, this is the first work exploring the molecular-level mechanism of lipid deposition during the growth and development stage of H. illucens larvae. The findings provide novel information for determining and utilizing the nutritional value of H. illucens larvae. Graphical Abstract: